Prevention of Bankruptcy of Industrial Enterprises and Organizations with State Participation - E. V. Gavrilin; S. V. Khetagurov (Управленческие науки)
The identification of cases of deliberate or fictitious bankruptcy of industrial sector organizations in the management of state enterprises and organizations is of great importance in ensuring economic security. The paper is devoted to the methodology of timely prevention of bankruptcy of state industrial enterprises and organizations and law enforcement practice in the field of bankruptcy. In the framework of risk management, the article analyzes the existing mechanisms for monitoring and identifying possible deterioration of financial and economic activity and the probability of bankruptcy of state industrial enterprises and organizations. The purpose of the work is to determine directions of the system development of combating unfair management decisions during the bankruptcy procedure, as well as the establishment of tools to prevent the bankruptcy of state industrial enterprises and organizations. There had been used the formal legal method in the paper, methods of complex and interdisciplinary analysis, as well as General scientific methods, including the dialectical method and the method of system analysis. As a result of the study, the main problems of law enforcement and managerial practice in detecting offenses during bankruptcy procedures are considered and the necessary areas of management and regulatory regulation are identified, an approach to identifying the threat of bankruptcy and implementing anti-crisis measures when managing state industrial enterprises and organizations is determined. The study may be of interest to public authorities in determining the methodological and regulatory framework, as well as strategies to improve the efficiency of management of state enterprises and organizations, and ensure economic security.